Analysis of The Impact of The Policy of Integration of Researchers Into Brin on The Development of Human Resources in The Field of Research - Khanan Yusuf; Vishnu Juwono (Publikasi Indonesia, 2024)
This article provides information on integrating researchers into Indonesia's National Research and Innovation Agency (BRIN). Discuss BRIN's objectives, plans for developing research resources, and collaboration with educational and research institutions. The document also mentions challenges national research faces in Indonesia, such as limited human resources for research. Integrating researchers into BRIN is a solution to improve the quality and quantity of research in Indonesia. BRIN aims to improve the quality and quantity of researchers in Indonesia by integrating researchers into its system. This integration involves cooperation with educational and research institutions at national and international levels. This article highlights the importance of human resources in research and the need to address expertise shortages in some complex regions. BRIN was established based on the merger of five institutions, including the Indonesian Institute of Sciences (LIPI) and the National Nuclear Energy Agency (BATAN). It also mentions the use of various research analysis methods, such as policy analysis and evaluative analysis, to assess the impact of policies and the implementation of research programs